PERAN PENDIDIKAN KELUARGA DALAM PEMBENTUKAN NILAI AGAMA MORAL ANAK USIA DINI - Diana Putri Amalia M (Early Childhood Teacher Education Department UNIVERSITAS SULTAN AGENG TIRTAYASA, 2019)
The family is the place where children get their education. Because children spend more time with family. Therefore as a parent must be able to provide positive stimulation to children. One aspect of development in early childhood is Religious and Moral Values. Most of what happens nowadays parents only emphasize developing children’s cognitive, but it should be noted again is the aspect of Moral Religious Values, because the technological sophistication is rapidly increasing, becoming one of the threats to the lack of family education about the value of moral religion given to children. As parents must develop aspects of moral religious values in children, this is very important given to children. Early childhood is a very vulnerable period, so it must be given positive stimulations, one of which is about the value of moral religion. This will be a provision for children to defend themselves with the development of the age in the 21st century which is at this time the era of the technological era continues to develop. So that with the formation of religious and moral values, children will do positive things in accordance with the teachings of Islam. Then the child will get happiness in the world and the hereafter. This is why the important role of faith-based family education is applied to early childhood.